2009
DOI: 10.1016/j.febslet.2009.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Binding of epigallocatechin‐3‐gallate to transthyretin modulates its amyloidogenicity

Abstract: a b s t r a c tMore than 100 transthyretin (TTR) variants are associated with hereditary amyloidosis. Approaches for TTR amyloidosis that interfere with any step of the cascade of events leading to fibril formation have therapeutic potential. In this study we tested (À)-epigallocatechin-3-gallate (EGCG), the most abundant catechin of green tea, as an inhibitor of TTR amyloid formation. We demonstrate that EGCG binds to TTR ''in vitro" and ''ex vivo" and that EGCG inhibits TTR aggregation ''in vitro" and in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 29 publications
6
123
0
Order By: Relevance
“…The results demonstrated that these phytochemicals disrupted pre-formed amyloid fibrils, though with different potency. EGCG powerfully disrupted mature TTR fibrils into a very polydisperse population of protein aggregates supporting results obtained for other amyloidogenic variants [13]. Curcumin markedly disaggregated amyloid fibrils, originating a particular population of small amorphous aggregates, morphologically similar to previously reported curcumin destabilized Ab fibrils [15].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results demonstrated that these phytochemicals disrupted pre-formed amyloid fibrils, though with different potency. EGCG powerfully disrupted mature TTR fibrils into a very polydisperse population of protein aggregates supporting results obtained for other amyloidogenic variants [13]. Curcumin markedly disaggregated amyloid fibrils, originating a particular population of small amorphous aggregates, morphologically similar to previously reported curcumin destabilized Ab fibrils [15].…”
Section: Discussionsupporting
confidence: 84%
“…Aliquots from the samples studied by DLS were also analyzed by TEM as previously reported [13,16]. Sample aliquots (5 ll) were adsorbed to carbon-coated collodion film supported on 200-mesh copper grids.…”
Section: Dynamic Light Scattering (Dls) and Transmission Electron Micmentioning
confidence: 99%
See 1 more Smart Citation
“…assessed by binding assays using control plasma 6, TTR alone was mainly fibrillar whereas the EGCG-containing preparations did not change [155]. Similarly, EGCG was found to inhibit TTR aggregation in media of a rat Schwannoma cell line, which secretes TTR Leu55→Pro, as determined by a filter-binding assay [155].…”
Section: Egcg: Egcg Interaction With Ttr Wasmentioning
confidence: 99%
“…Since then, it has been shown that EGCG binds directly to a large number of proteins that are involved in protein misfolding diseases and that EGCG inhibits their fibrillization. Examples include αS [81,82], Aβ [36,82], transthyretin [83], lysozyme [84], the prion protein PrP [85], and the yeast prion Sup35 [86].…”
Section: Mechanism Of Egcg Interventionmentioning
confidence: 99%